2022
DOI: 10.1021/acs.jpcc.2c00342
|View full text |Cite
|
Sign up to set email alerts
|

Insight into Subsurface Adsorption Derived from a Lattice-Gas Model and Monte Carlo Simulations

Abstract: Theoretical gas-surface models that describe adsorption over a broad range of adsorbate concentrations can provide qualitative insight into chemical phenomena, such as subsurface adsorption, surface reconstruction, and industrial heterogeneous catalysis. However, most atomistic, quantum-mechanical models of gas-surface adsorption are limited to low adsorbate coverage due to the large computational cost of models built using many surface atoms and adsorbates. To investigate adsorption in the subsurface of a cry… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 60 publications
2
8
0
Order By: Relevance
“…At increasing values of P H 2 S / P H 2 , an ordered phase having a sulfur coverage of 0.37 ML is noted on p(4 × 4) Pt(111). Similar ordered phases with a coverage of 0.37 ML have been observed for O* adsorbed on the surface of Ag(111), prior to the formation of subsurface Ag x O y phases . At the highest values of P H 2 S / P H 2 , a p(2 × 1)-1S* ordered phase is stabilized at a sulfur coverage of 0.50 ML.…”
Section: Resultssupporting
confidence: 69%
See 1 more Smart Citation
“…At increasing values of P H 2 S / P H 2 , an ordered phase having a sulfur coverage of 0.37 ML is noted on p(4 × 4) Pt(111). Similar ordered phases with a coverage of 0.37 ML have been observed for O* adsorbed on the surface of Ag(111), prior to the formation of subsurface Ag x O y phases . At the highest values of P H 2 S / P H 2 , a p(2 × 1)-1S* ordered phase is stabilized at a sulfur coverage of 0.50 ML.…”
Section: Resultssupporting
confidence: 69%
“…The ab initio phase diagrams in Figure reveal that ordered arrangements of S* involving adsorption of S* in high-symmetry configurations on the Pt sites on p(4 × 4) Pt(111) and p(4 × 4) Pt(100) emerge as the most stable phases. Such ordered structures have been reported for adsorbates like H*, O*, C*, and CO* , that are anchored on late transition metals and in structures of NaAl alloys . The atomic level details of these ordered structures are confirmed using a combination of low-energy electron diffraction spectroscopy, lattice gas Hamiltonians used together with grand canonical Monte Carlo simulations, , and with first-principles methods like DFT .…”
Section: Resultsmentioning
confidence: 70%
“…48,49 This being said, a few studies have reported on the binding energy of atomic oxygen on silver referenced to the gas phase oxygen atom. 50–52 On the Ag 13 cluster, this binding energy is really large (−3.5 eV per atom). 51 This is equivalent when atomic oxygen is adsorbed on Ag(111) at low coverage (≈−3.5 eV per atom) 50–52 and this remains strong even at saturation (≈−2 eV per atom for 1 ML).…”
Section: Resultsmentioning
confidence: 99%
“…50–52 On the Ag 13 cluster, this binding energy is really large (−3.5 eV per atom). 51 This is equivalent when atomic oxygen is adsorbed on Ag(111) at low coverage (≈−3.5 eV per atom) 50–52 and this remains strong even at saturation (≈−2 eV per atom for 1 ML). 50 Hence, the two likely candidates for modeling Ag NP contamination are strongly bound species, even at high coverage for atomic oxygen.…”
Section: Resultsmentioning
confidence: 99%
“…Although advances in periodic DFT allow quantum mechanical calculations of adsorption properties at low adsorbate concentrations with high accuracy and efficiency, the huge computational cost makes it impossible to use it for direct sampling of large substrate configuration spaces and long-time scales. 39 The chemically meaningful and flexible cluster expansion method is a powerful theoretical approach to studying the effect of adsorbate interactions as coverage increases, which is a convenient way to bridge the gap between the accuracy of ab initio calculations and the computational efficiency required to sample a large configuration space. The role of adsorbates was introduced into CE by building a model with specific adsorbent coverage and setting the training set accordingly.…”
Section: Introductionmentioning
confidence: 99%